Ecos de arcaicas cosmogonías acuáticas en el ocaso del mundo medieval - Marcos Casquero, Manuel-Antonio (’Ilu. Revista de Ciencias de las Religiones, 2009)
We review primitive cosmogonies legends from different cultures in which the water plays a fundamental role in the creation of the world. We analyze the main properties of the water appearing in these legends, the cult to water from ancient times until the end of the Middle Ages, and the relationship of water with magic.